Empowerment of Dasawisma and Health Cadres as Family Cadres to Optimize Family Posyandu - Fitriadi, Yogi; Mahmudah, Noor Afif; Ekawati, Fitriana Murriya; Fauziah, Siti Rizki; Ngang, Inggong; Nababan, Adelina Novita; Claramita, Mora (Review of Primary Care Practice and Education, 2024)
Background: Health cadres are one of the important elements in realizing health in society. In the North Lombok region, the change in the status of ordinary Posyandu to family Posyandu makes health care in the community more comprehensive for all family members. For this reason, efforts to increase the capacity of health cadres are important to improve health status in the family sphere. Objective: This study aims to see the effect of training on increasing the capacity of family cadres on the knowledge of family cadres in the North Lombok Regency area. Method: The sampling process is carried out using the cluster sampling method where each village representative in the Kayangan sub-district of North Lombok Regency sends a cadre representative to train to increase the capacity of Dasawisma cadres to become family cadres. A descriptive analysis of respondents' characteristics and differences in knowledge scores before and after family cadre training activities were conducted. The data analysis process was carried out with the Wilcoxon Test because the data distribution was abnormal. Result: Thirty-three health cadres meet the inclusion and exclusion criteria. The results showed that the median value (maximum-minimum) of family cadres before training, shortly after training and six months after training was 66.67 (36.67-80), 66.67 (53.33-83.33) and 70 (53.33-96.67). From the Wilcoxon test, there was a statistically significant difference between the knowledge score before training and six months after training (p<0.05). There was no statistically significant difference between the knowledge score before training and shortly after training, as well as the knowledge score shortly after training and 6 months after training (p>0.05). Conclusion: Family cadre empowerment training can improve knowledge scores 6 months after training, but there is no significant difference in knowledge score improvement shortly after training as well as between knowledge scores shortly after training and 6 months after training.